Thermochromic VO2 for energy-efficient smart windows - Cui, Yuanyuan (2020)
Rapid development of the thermochromic glazing technique promises next-generation architectural windows with energy-saving characteristics by intelligently regulating indoor solar irradiation via modulating windows’ optical properties in response to the surrounding temperature. Vanadium dioxide (VO2) is a promising material for energy-saving smart windows due to its reversible metal-to-insulator transition near room temperature and accompanying large changes in its optical properties. This review provides a comprehensive overview of the application of VO2 to smart windows with particular emphasis on recent progress from the electronic, atomic, nano, and micron perspectives. The effects of intrinsic atomic defects, elemental doping, and lattice strain on VO2 nanocrystals are examined. Nano- and microscale morphology engineering approaches that aim to enhance the thermochromic performance and impart practical multi-functionalities are summarized. Finally, the challenges and future directions of VO2-based smart windows are elaborated to bridge the gap between the lab research and large-scale practical applications. Vanadium dioxide (VO2) is a promising material for energy-saving smart windows due to its reversible metal-to-insulator transition near room temperature. This thermally induced phase transition is reversible, and it is accompanied by a dramatic change in the optical properties in the near-infrared region from a low-temperature transparent state to a more blocking state at high temperatures, imbuing the VO2-based window with the ability to regulate solar heat flux by responding to temperature automatically. In this review, the progress in VO2-based smart windows is overviewed, from the band structure designing at the electronic and atomic scales to morphology engineering from nano- to microscales. We discuss the effects of intrinsic atomic defects, elemental doping, and lattice strain on the electronic and atomic structures of VO2. Subsequently, nano- and microscale engineering methods to enhance the performance of smart windows are presented, including incorporating particles, tuning the porosity, designing nanocomposites, developing biomimetic patterns, creating grids, and applying multifunctional antireflection coatings. The energy efficiency is also discussed from both simulations and experimental aspects. Lastly, challenges and future directions are discussed. We hope that this work may inspire more innovative progress and accelerate the development of this technique from the lab to industry. VO2 is a promising material for energy-saving smart windows due to its reversible metal-to-insulator transition near room temperature and accompanying large changes in its optical properties. This review provides a comprehensive overview of the application of VO2 to smart windows with particular emphasis on recent progress from the electronic, atomic, nano, and micron perspectives. The challenges and future directions of VO2-based smart windows are elaborated to bridge the gap between the lab research and large-scale practical applications.